Modeling and Simulation of an Electromagnetic Energy Harvesting System - Pecioski, Damjan; Shishkovski, Dejan; Ignajatovska, Anastasija Angjusheva; Markovska, Simona Domazetovska; Gavriloski, Viktor (IEEE, 2024)
Low-power electronic devices can be powered using the concepts of micro-scale energy harvesting techniques to ensure a near-infinite lifetime work cycle. Nonetheless, this conversion of energy is not ideal and as a result, there is always a certain percentage of wasted energy. One must strive that the modeling and simulation of these systems is as close as possible to the real systems and conditions. Within this paper, an electromagnetic energy harvesting system that is attached to an elastic mechanical structure in the form of a cantilever beam has been developed. A mathematical model for the structure and the linear electromagnetic generator has been derived. The simulations concerning the obtained model have been conducted using the Matlab/Simulink software package. Finally, an experimental model has been created to validate the prior acquired results from the simulation.
Keywords: Coils , Analytical models , Actuators , Software packages , Mathematical models , Generators , Energy harvesting